Description of lithologic section units of IODP Hole 389-M0106A - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Description of lithologic section units from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The content of this dataset is based on the visual core descriptions (VCD) done by sedimentologists during the onshore phase of expedition 389 (2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen). For digitalization of the information, content of the hand-drawn VCD sheets was transferred into the mobile Drilling Information System (mDIS) database. The present dataset forms the basis for the digital lithologic columns and composite plots archived under the titles Visual core description of IODP Hole 389-M00###. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025